Serum Vitamin E is Associated with Osteoarthritis among Korean Older Adults - Park, Seonghee; Kim, Kyeong-Rae; Kwon, Hana; Lee, Kwang-Yeol; Jang, Il-Tae (Central Asian Journal of Medical Sciences, 2022)
Objectives: We aimed to examine the cross-sectional association between serum vitamin E level and osteoarthritis in Korean older adults. Methods: Data from the Korea National Health and Nutrition Examination Survey 2016 – 2018 were used. Overall, 978 participants aged ≥ 65 years were included in the study. Demographic, lifestyle, and health data were obtained through interviews or self-reported questionnaires. Patients with osteoarthritis were defined if they had responded “yes” to any of these three questions related to diagnosis, current condition, and treatment. Multivariate logistic regression analysis was performed to assess the association between serum vitamin E level and osteoarthritis. Results: After multivariate adjustment, a higher level of vitamin E was found to be associated with a higher prevalence of osteoarthritis (Odds ratio: 2.27, 95 % Confidence Interval: 1.19 – 4.34, p for trend = 0.037). Conclusion: A higher level of serum vitamin E was associated with increased osteoarthritis prevalence in older Koreans. Further prospective or clinical studies are needed to verify the causality.